KAJIAN NAMA DAN PENEMPATAN UKIRAN MINANGKABAU SERTA KALIGRAFI ARAB PADA MASJID JABAL RAHMAH SEMEN PADANG - PRIMA YUSAPUTRA, Ir. Drs. Heldi, M.Si. Ph.D., Drs. Jamilus, M.Pd., Ph.D. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Jabal Rahmah Mosque in Semen Padang is a mosque that has a lot of variations in Minangkabau and Arabic calligraphy carving. This empirical conditions raises two questions: “What is the name of the minangkabau and Arabic calligraphy carving in Jabal Rahmah Semen Padang Mosque” and “ Where is Minangkabau and Arabic calligraphy carvings placed in Jabal Rahman Semen Padang Mosque”. This study aims to identify the name and to describe the placement of the Minangkabau and Arabic Calligraphy Carving in Jabal Rahmah Semen Padang Mosque. The research Method used in this study is descriptive qualitative. The results of this study finds that there are three kinds of Minangkabau Carving, those are (1) Kuciang Lalok (2) Tirai Bungo Intan, (3) Tupai Tatagun. This study also finds that there are two types of calligraphy on the mosque, those are Naskhi Khat and Tsulus Khat. The placement of the Carving and Calligraphy in this mosque cover many places of the mosque, The entrance of the Mosque, windows, ceilings, walls,liwan and mihrab of the mosque. Through this research the researcher expects that this research can be a positive contribution to the preservation of Indonesian culture to the next generation without losing local knowledge of local culture.Keywords: Mosque, Carving, Calligraphy, Minangkabau